The lived experience of leaving a Muslim marriage, as experienced by Muslim women in South Africa - Samodien, Zeenat (Department of Sociology, 2024)
The lived experience of leaving a Muslim marriage, as experienced by South African Muslim women is the focus of this master's thesis. Using a qualitative research design approach, four Muslim women from Cape Town, KwaZulu-Natal and Johannesburg were interviewed to learn more about leaving a marriage as a Muslim woman in South Africa. The findings revealed that the women sought divorce due to experiences of intimate partner violence, which included various forms of abuse, particularly economic abuse, social isolation, and physical abuse. This thesis employs an Islamic feminist approach, understanding these forms of abuse as rooted in patriarchal misinterpretations of religious text and ‘classical' Fiqh operating as ‘objective religious knowledge' in the contemporary moment. With an Islamic feminist approach, the findings further revealed the ways women resisted the various forms of abuse. These ranged from personal strategies of resistance in which the women aimed to manage and prevent further abuse whilst remaining in the marriage, to seeking external assistance from Muslim judicial councils, family, and friends in an attempt to exit the marriage. In the context of the nonrecognition of Muslim marriages, the findings reveal that Muslim women are left unprotected, unable to access their rights as Muslim women from the Muslim judicial councils, and unable to turn to the state for protection. Based on the experiences shared by the women interviewed, their friends and family proved critical in ensuring a safe exit from the abusive marriage. This research contributes to the limited academic material prioritising the lived experiences of Muslim women in South Africa, particularly related to Muslim marriage, divorce, and experiences of abuse in South African Muslim communities.